Conceptual framework for balancing society and nature in net-zero energy transitions. Issue 125 (November 2021) - Delafield, Gemma; Donnison, Caspar; Roddis, Philippa; Arvanitopoulos, Theodoros; Sfyridis, Alexandros; Dunnett, Sebastian; Ball, Thomas; Logan, Kathryn G.
Abstract: Transitioning to a low carbon energy future is essential to meet the Paris Agreement targets and Sustainable Development Goals (SDGs). To understand how societies can undertake this transition, energy models have been developed to explore future energy scenarios. These models often focus on the techno-economic aspects of the transition and overlook the long-term implications on both society and the natural environment. Without a holistic approach, it is impossible to evaluate the trade-offs, as well as the co-benefits, between decarbonisation and other policy goals. This paper presents the Energy Scenario Evaluation (ESE) framework which can be used to assess the impact of energy scenarios on society and the natural environment. This conceptual framework utilises interdisciplinary qualitative and quantitative methods to determine whether an energy scenario is likely to lead to a publicly acceptable and sustainable energy transition. Using the SDGs, this paper illustrates how energy transitions are interconnected with human development and the importance of incorporating environmental and socio-economic data into energy models to design energy scenarios which meet other policy priorities. We discuss a variety of research methods which can be used to evaluate spatial, environmental, and social impacts of energy transitions. By showcasing where these impacts will be experienced, the ESE framework can be used to facilitate engagement and decision-making between policymakers and local communities, those who will be directly affected by energy transitions. Outputs of the ESE framework can therefore perform an important role in shaping feasible and energy transitions which meet the Paris Agreement targets and SDGs. Highlights: Energy models do not give sufficient attention to social and environmental impacts. Our ESE framework uses an interdisciplinary approach to energy scenario evaluation. Using multiple methods, the ESE framework considers how impacts vary spatially. A social licence to operate will be key to the success of net-zero transitions.